The potential molecular mechanism underlying gypenoside amelioration of atherosclerosis in ApoE−/− mice: A multi-omics investigation - Xing Ju; Yufeng Liu; Ying Wang; Guoyuan Sui; Yixin Ma; Huimin Cao; Yuan Cao; Jin Wu; Ying Du; Xue Leng; Lianqun Jia; Guanlin Yang (Heliyon, 2024)
Gypenosides (Gyp) are bioactive components of Gynostemma pentaphyllum that have a variety of pharmacological properties. Extracts of G. pentaphyllum have been found to be effective in the reduction of blood sugar and lipids and prevention of atherosclerosis. Here, the functions of Gyp and the mechanisms underlying their effects on atherosclerosis were investigated. Mice were allocated to three groups, namely, the control (C57BL/6), atherosclerosis model (ApoE−/− mice with high-fat diet), and Gyp-treated groups. Differentially expressed mRNAs, miRNAs, circRNA, and differential metabolites among the groups were analyzed. The results showed that “Fatty acid metabolism”, “Fatty acid elongation”, “Cytokine-cytokine receptor interaction”, and “PI3K-Akt signaling pathway”, amongst others, were involved in treatment process. Differentially expressed genes, including Fabp1, Apoe, FADS1, ADH1, SYNPO2, and Lmod1were also identified. Mmu-miR-30a and mmu-miR-30e showed reduced expression in atherosclerosis models but were increased following Gyp treatment, suggesting involvement in the effects of Gyp. In addition, chr5:150604177-150608440 were found to interact with mmu-miR-30a and mmu-miR-30e to regulate their abundance. In terms of metabolomics, Gyp may regulate biological processes involving PGD2 and PGJ2, potentially alleviating atherosclerosis. In conclusion, Gyp appeared to have complex effects on atherosclerosis, most of which were positive. These results support the use of Gyp in the treatment of atherosclerosis.